Photoelectric Dual Control Negative Differential Resistance Device Fabricated by Standard CMOS Process - Jia Cong; Luhong Mao; Sheng Xie; Fan Zhao; Dong Yan; Weilian Guo (IEEE Photonics Journal)
To prepare a desired negative differential resistance (NDR) device by standard complementary-metal–oxide–semiconductor (CMOS) process, a photoelectric dual control NDR device with a PNP bipolar-junction-transistor (BJT) and an NPN BJT was designed and fabricated by using the Si-base standard 0.18 μm CMOS process without any process modification and a special substrate. In order to reduce the valley current under optical control, a metal mask was added to the NDR device. The results show that the device exhibits good NDR characteristics under either voltage-control or photo-control. Under voltage-control, a low volley current (0.23 pA) and a high peak-to-valley current ratio (1.4 × 1010) are obtained at less than 1 V. Under photo-control, the two parameters obtained at less than 0.5 V, are 37 nA and 4827, respectively. Also, the device displays fine S-type NDR characteristics and nice maintaining response function under photo-control. These superior photoelectric NDR characteristics endow the device with greatly potential application in the photoelectric logic circuits.